2018
DOI: 10.1039/c7ib00199a
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional in vitro dynamic micro-tissue model of cardiac scar formation

Abstract: In vitro cardiac models able to mimic the fibrotic process are paramount to develop an effective anti-fibrosis therapy that can regulate fibroblast behaviour upon myocardial injury. In previously developed in vitro models, typical fibrosis features were induced by using scar-like stiffness substrates and/or potent morphogen supplementation in monolayer cultures. In our model, we aimed to mimic in vitro a fibrosis-like environment by applying cyclic stretching of cardiac fibroblasts embedded in three-dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 39 publications
3
45
0
Order By: Relevance
“…In addition to engineered normal cardiac tissues on chip, establishment of in vitro pathological tissue models is crucial for applications in diseases studies and drug development. A hydrogel‐based cardiac scar‐on‐a‐chip model was developed to recapitulate the key features of scar formation including fibroblast proliferation and activation, ECM deposition and stiffening . In another study, neonatal cardiac fibroblasts were embedded in 3D fibrin hydrogels, then applied with mechanical stimulation (cyclic stretching) to mimic a fibrosis‐like environment .…”
Section: Hydrogels In Organs‐on‐a‐chip Engineeringmentioning
confidence: 99%
“…In addition to engineered normal cardiac tissues on chip, establishment of in vitro pathological tissue models is crucial for applications in diseases studies and drug development. A hydrogel‐based cardiac scar‐on‐a‐chip model was developed to recapitulate the key features of scar formation including fibroblast proliferation and activation, ECM deposition and stiffening . In another study, neonatal cardiac fibroblasts were embedded in 3D fibrin hydrogels, then applied with mechanical stimulation (cyclic stretching) to mimic a fibrosis‐like environment .…”
Section: Hydrogels In Organs‐on‐a‐chip Engineeringmentioning
confidence: 99%
“…The reversibility of this low-oxygen-induced condition was confirmed by the fact that the subsequent treatment with fresh growth medium and high-oxygen tension partially recovered CM organization and electrical functionality. Concomitantly, we observed that fibroblasts switched their phenotype towards myofibroblasts as usually observed during cardiac remodeling inflammatory/repair processes (Diaz-Flores et al, 2015;Li et al, 2015;Occhetta et al, 2018). A similar 2D model had never been developed, and can be a useful screening tool for testing and screening therapeutic factors.…”
Section: Discussionmentioning
confidence: 52%
“…This condition is different from the ischemia-reperfusion injury in which, following ischemia, the sudden restore of the oxygen levels by reperfusion could paradoxically cause more damage to the cardiomyocytes due to multifactorial mechanisms (as calcium overload and reactive oxygen species overproduction; Kalogeris, Bao, & Korthuis, 2014). Concomitantly, we observed that fibroblasts switched their phenotype towards myofibroblasts as usually observed during cardiac remodeling inflammatory/repair processes (Diaz-Flores et al, 2015;Li et al, 2015;Occhetta et al, 2018). Second, this 2D model was used to investigate the potential SVF paracrine effect on chronic hibernating CM, evaluating the consequent CM recovery in morphology and functionality.…”
Section: Discussionmentioning
confidence: 55%
“…In addition to thrombosis, fibrosis has also been modeled in vitro through the application of cyclic mechanical stretching to cell‐laden hydrogels, resulting in fibroblast differentiation, matrix protein deposition, ECM stiffening, and remodeling of scar tissue. [ 332,341,342 ] These in vitro mechanistic studies which can elucidate the role of biophysical forces in driving aberrant cardiovascular pathologies have significant potential for the development of life‐saving interventions and clinical translation from bench to bedside. [ 340,343 ] However, further mechanistic insight into the developmental stages of cardiac disorders needs to be obtained via the use of cardiac‐specific ECs or hiPSC‐derived ECs differentiated toward cardiac‐specific phenotype and their functional incorporation in microphysiological systems.…”
Section: Modeling Vascular Mechanopathology In Vascularized Microphysmentioning
confidence: 99%